2023
DOI: 10.1108/sjme-09-2022-0201
|View full text |Cite
|
Sign up to set email alerts
|

Trust, convenience and environmental concern in consumer purchase intention for organic food

Abstract: Purpose The customers are demanding the products which are not only healthy but also clean and environment friendly i.e. call for sustainable consumption products. Therefore, this study aims to identify the important drivers of organic food purchase intention. Design/methodology/approach A cross-sectional research design involving the collection of primary data from 234 respondents was adopted in this study. Responses were gathered from the consumers of organic food representative of the Indian population. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 123 publications
2
1
0
Order By: Relevance
“…This sense of responsibility motivates them to be a demographic that not only engages in pro-environmental actions but also promotes such consumption behaviors among their peers [2,11,36]. This finding aligns with the conclusions of several researchers who have identified that attitude is a crucial determinant of both the intention to purchase and the actual purchasing behavior for organic products [1,2,4,11,20,22,27,32,53,54], and it is closely associated with GPB [3,7]. Conversely, it challenges the assertions of previous studies which cast doubt on the influential role of attitude in GPB [17], particularly those positing an attitude-behavior gap where consumers with EAT do not consistently purchase organic products [16,31], highlighting discrepancies between their stated beliefs and actions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This sense of responsibility motivates them to be a demographic that not only engages in pro-environmental actions but also promotes such consumption behaviors among their peers [2,11,36]. This finding aligns with the conclusions of several researchers who have identified that attitude is a crucial determinant of both the intention to purchase and the actual purchasing behavior for organic products [1,2,4,11,20,22,27,32,53,54], and it is closely associated with GPB [3,7]. Conversely, it challenges the assertions of previous studies which cast doubt on the influential role of attitude in GPB [17], particularly those positing an attitude-behavior gap where consumers with EAT do not consistently purchase organic products [16,31], highlighting discrepancies between their stated beliefs and actions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 85%
“…This sense of responsibility motivates them to be a demographic that not only engages in pro-environmental actions but also promotes such consumption behaviors among their peers [2,11,36]. This finding aligns with the conclusions of several researchers who have identified that attitude is a crucial determinant of both the intention to purchase and the actual purchasing behavior for organic products [1,2,4,11,20,22,27,32,53,54], and it is closely associated with GPB [3,7]. Conversely, it…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Research by Aertsens et al [24] found a significant positive correlation between consumer attitudes and their consumption of organic foods. Similarly, Von Meyer et al [67] and Prakash et al [68] identified a direct, meaningful relationship between attitude and purchasing behavior among German consumers. Kumar et al [8] suggested that a favorable attitude towards environmental and organic products mediates the effect of environmental knowledge on purchasing decisions.…”
Section: Attitudementioning
confidence: 88%
“…Health consciousness is a primary factor, as consumers are motivated by concerns over the potential APJML health risks associated with pesticides and chemicals in conventionally grown produce, with organic options perceived as safer (Hempel and Hamm, 2016;Ranjbarshamsi et al, 2016;Ceylan et al, 2018). Ethical considerations also play a role, with consumers feeling a sense of moral responsibility to support environmentally friendly products (McEachern and McClean, 2002;Cho and Krasser, 2011;Prakash et al, 2023). Economic development and environmental awareness in developing countries have further influenced consumer attitudes towards organic food (Yang et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%